Joaquin torres-garcía’s constructive universalism (2005)
The purpose of this article is to examine in detail theformulation and development of Joaquin Torres-García’sConstructive Universalism. In order to do so I analyseTorres-García’s interpretation and appropriation ofCubism, Neoplasticism, and Surrealism, the main sourcesfrom which he nurtured his personal vision of art. Thus,I conclude by providing a definition of ConstructiveUniversalism, showing the influences it draws from theEuropean context, but also emphasising the originalityof the style. I also present briefly the development ofthis artistic programme after the artist left Paris andestablished in Uruguay, and its influence upon LatinAmerican art.